Some Preliminary Notes on an Empirical Test of Freud’s Theory on Depression - Desmet, Mattias (Frontiers in Psychology, 2013)
A review of the literature indicates that empirical researchers have difficulty translating Freud’s theory on depression into appropriate research questions and hypotheses. In their attempt to do so, the level of complexity in Freud’s work is often lost. As a result, what is empirically tested is no more than a caricature of the original theory. To help researchers avoid such problems, this study presents a conceptual analysis of Freud’s theory of depression as it is presented in Mourning and Melancholia (Freud, 1917). In analyzing Freud’s theory on the etiology of depression, it is essential to differentiate between (1) an identification with the satisfying and frustrating aspects of the love object, (2) the inter- and an intrapersonal loss of the love object, and (3) conscious and unconscious dynamics. A schematic representation of the mechanism of depression is put forward and a research design by which this schema can be empirically investigated is outlined.